The prevalence of frontal sinus agenesis (aplasia) among Kurdish populations of Erbil city. - Soran M Karim (Erbil Dental Journal)
Background and objective: The frontal bone contains a pair of air-filled hollow cavities called frontal sinuses, the size, shape and anatomic measurements and dimensions of the frontal sinuses are determined by the degree of its pneumatization. Any disturbance to the sinus during its early development stages could results whether in hypoplasia (underdevelopment) or aplasia (total lack) of the sinus either unilaterally or bilaterally. This study aims to investigate the prevalence of aplasia of the frontal sinus among Kurdish populations of Erbil city, in addition to assessment of the type of aplasia and gender impact on the condition if there is any. Methods: This retrospective/radiological study was conducted on randomly selected PA (Caldwell view or occipito-frontal) plain radiographic images of 512 Kurdish individuals of mixed genders, ages rangeing between 18 to 64 years and images were taken from the periods between April 2020 to May 2022. Results: Careful examination of 512 assessed PA radiographs (with patient’s ages ranging between 18 to 65 years) showed agenesis of the frontal sinus in 26 cases (5.16 %), 17 females and 9 male cases), the type and location of the agenesis varied greatly as it was bilateral agenesis type only in 7 cases, and unilateral in remaining 19 cases, among the unilateral sinus agenesis cases 2 were observed to be agenesis of the left and 17 of the right frontal sinuses respectively.